The Implementation of Linear Program in Determining Product Combinations to Achieve Optimal Profits in Nganjuk “Syukur” Tile Home Industry - Sinollah, Sinollah (Jurnal Entrepreneur dan Entrepreneurship, 2020)
The objective achieved through this research is to study the application of linear programming in determining the combination of products that can produce optimal profits in the Nganjuk "thanksgiving" tile home industry. To achieve these objectives, in this study using this research included in descriptive research, the main data collection methods are interviews, field observations and documentation. Analysis of the data used is linear programming analysis with the simplex method. While to determine the agreement of use, a time series analysis can be used which can be used as a basis for forecasting for the future (linear trend with the method of small squares). From the results of the analysis to determine the optimal product combination in linear programming, there is a function as an objective and a function as a limitation. And in this study it was confirmed as follows: Max Z = 216,250 X1 + 156,000 X2 + 1,363,000 X3. As a combination of tile (X1) = 341 per day; Pilang Karang Tile (X2) = 448 per day and Wuwung Tile (X3) = 203 per day, the benefit is Rp. = 418,937,000. For that, the company must pay attention to the combination of products by calculating the right, if the company produces more than one type of product. Likewise with the limiting factors. Keywords: Linear Program, Product Combination, Optimal Profit, Home Industry